지속적인 리팜핀 초치료와 관련된 급성 간질성 신염 - 김현정; Hyun Jung Kim; 차정민; Jeong Min Cha; 정덕은; Duk Eun Jung; 이지은; Ji Eun Lee; 이유민; Yu Min Lee; 변승재; Seung Jae Byun; et al. (Kidney research and clinical practice, 2008)
Acute renal failure caused by rifampin typically occurs on intermittent administration or reintroduction of the drug. However, acute kidney injury (AKI) due to rifampin has been rarely reported to occur in patients receiving a continuous rifampin therapy. We have experienced a case of acute interstitial nephritis during the first course of standard anti-tuberculous therapy, including continuous rifampin therapy in daily dose. Forty-five-year-old male, who had been being treated with anti-tuberculous medication including rifampin (600 mg/day), was admitted to our hospital because of generalized edema and dyspnea by acute renal failure. His past medical history was unremarkable. Since the creatinine level was still elevated in 10 days after cessation of rifampin, we performed renal biopsy. The renal pathologic findings revealed acute interstitial nephritis. After that, the patient symptom was relieved and serum creatinine level was decreased without specific therapy. The renal function was recovered at 1 month after withdrawal of rifampin. We report a case of acute interstitial nephritis complicated with the first daily rifampin therapy, along with the review of literature.